The Effect of Internal Control, Organizational Commitment, and Utilization of Information Technology on the Quality of Financial Statements with Organizational Culture as a Moderating Variable - Fariz Akbar; Fachruzzaman; Lismawati (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the effects of internal control, organizational commitment, and information technology (IT) utilization on the quality of financial statements, with organizational culture as a moderating variable. Grounded in stewardship and task-technology fit theories, survey data were collected from 120 financial personnel across 40 Regional Work Units (SKPD) in Central Bengkulu Regency and analyzed using PLS-SEM. The results indicate that internal control (β=0.231, p=0.004), organizational commitment (β=0.272, p=0.004), and IT utilization (β=0.320, p=0.001) significantly and positively affect the quality of financial statements. Furthermore, organizational culture acts as a pure moderator that significantly strengthens the impact of internal control (β=0.242, p=0.012), organizational commitment (β=0.231, p=0.003), and IT utilization (β=0.315, p=0.002). The model accounts for 88.9% of the variance in financial statement quality (R²=0.889). These findings imply that technical systems and behavioral factors produce optimal reporting outcomes when embedded within an accountability-driven institutional culture.